OPEN REDUCTION AND INTERNAL FIXATION WITH PLATING VERSUS EXTERNAL FIXATOR IN DISTAL END RADIUS FRACTURES: A COMPARATIVE STUDY - SATYANARAYANA Y; SIVAKUMAR C; RAVI PRAKASH D; HEMANTH REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The purpose of this study is to compare the external fixation and locking plate fixation of intraarticular fractures of the distal radius in terms of functional outcome and complications. The study aims to assess the patients for fracture union, wrist range of motion (ROM), grip strength, pain, and activity among the locking plate and external fixator group. Methods: This study aimed to compare distal end radius external fixator to distal end radius plating regarding functional outcomes. This is an observational type of study where 40 patients were included in the study, among them, 20 were treated with external fixator/k wire and 20 with distal radius plate. The study was conducted in a tertiary care institute during the study period. Results: The most patients were males >50 years of age, with injury caused by a fall on an outstretched hand. In the present study, we got excellent functional results according to the G and O’Brien system in 11 (55%) of patients treated with the plating group, good results in 5 (25%), fair results in 4 (20%), and poor (0%) in the plating. Conclusion: Plating provides better functional outcomes, as assessed by Green and O’Brien’s score, as compared to external fixation. It allows for an early post-operative ROM exercises compared to an external fixator and better anatomical positioning of the fracture segments.